Web security for network and system administrators - Mackey, David (Course Technology, 2003)
Topics covered in this text include network security, operating system security and auditing, and attack and threat analysis. It should be of interest to webmasters wishing to develop their knowledge of security issues, as well as individuals studying for the CIW Security Profession.